Carbofuran induces increased anxiety-like behaviors in female zebrafish (Danio rerio) through disturbing dopaminergic/norepinephrinergic system. (August 2020) - Liu, Shuang; Yu, Miao; Xie, Xincen; Ru, Yiran; Ru, Shaoguo
Abstract: Carbofuran, a carbamate pesticide, is widely used in developing countries to manage insect pests. Studies have found that carbofuran posed potential risks for the neurotransmitter systems of non-target species, we speculated that these disruptive effects on the neurotransmitter systems could trigger anxiety-like behaviors. In this study, female zebrafish were exposed to environmental levels (5, 50, and 500 μg/L) of carbofuran for 48 h to evaluate the effects of carbofuran on anxiety-like behaviors. Results showed that zebrafish exhibited more anxiety-like behaviors which proved by the observed higher bottom trend and more erratic movements in the novel tank after carbofuran treatment. In order to elucidate the underlying molecular mechanisms of carbofuran-induced anxiety-promoting effects, we measured the levels of neurotransmitters, precursors, and major metabolites, along with the level of gene expression and the enzyme activities involved in neurotransmitter synthesis and metabolism. The results demonstrated that acute carbofuran exposure stimulated the mRNA expression and enzyme activity of tyrosine hydroxylase, which sequentially induced the increased levels of dopamine and norepinephrine. Tyrosine hydroxylase inhibitor relieved the anxiety-related changes induced by carbofuran, confirming the overactive tyrosine hydroxylase-mediated accumulation of dopamine and norepinephrine in the brain was one of the main reasons for carbofuran-induced anxiety-like behaviors in the female zebrafish. Overall, our study indicated the environmental health risks of carbamate pesticide in inducing neurobehavioral disorders and provided novel insights into the investigation of the relevant underlying mechanisms. Highlights: Acute carbofuran exposure increased anxiety-like behaviors in female zebrafish. Carbofuran exposure disturbed neurotransmitter systems. Dopaminergic/norepinephrinergic system was responsible for increased anxiety-like behaviors.